Az alkalmi munkavállalói könyvvel történő foglalkoztatás jellemzői: egy 2008. áprilisi kérdőíves munkavállalói adatfelvétel eredményei - András Semjén; István János Tóth; Ágnes Makó (Hungarian Academy of Sciences, Institute of Economics, 2008)
– The paper investigates the socio-demographic characteristics and the labor market history of casual workers that have been temporarily employed for some time using a temporary work booklet (ensuring favorable tax treatment for casual workers and their employers). By investigating that, as well as the involvement of these casual workers in the hidden economy, the authors try to explore the contradictory impacts of this special tax treatment of temporary employment. After explaining the sampling method and depicting some main characteristics of the sample, the paper describes the links between labor market vulnerability, temporary employment and hiding or underreporting of labor income. For those employed with the temporary work booklet black or grey employment is an ordinary phenomenon, visibly present in everyday life. As the actual administrative rules concerning the use of the booklet in case of temporary employment provide ample opportunities for unreporting or underreporting of employment periods and income at a relatively low risk of detection and punishment, in some cases employers try to convert normal employment status into temporary employment thus taking advantage of the booklet in order to reduce their tax payments. Thus paradoxically the booklet, conceived as a policy tool for reducing hidden employment may even foster the underreporting of income. However, although abusing the booklet is not rare, our results (though not convincing enough statistically) may indicate that using the booklet to at least partially regularize former hidden employment is more widespread. In some cases where the booklet is abused during a probation period, employment may also be regularized later. Our results indicate that the relationship between educational attainment or income and involvement in unreported work and/or underreporting of income is ambiguous and non-linear in this 6 segment of the labor market. Masking labor income as entrepreneurial income from subcontracting can be mostly found amongst workers above a certain level of educational attainment; it is also more common amongst middle income employees, while it is atypical for low and high earners. On the other hand, unreported direct cash payments to employees are more frequent amongst low and high earners, while occur relatively rarely in the middle income range. Our results suggest that experiencing unemployment spells directly (by the employee) or indirectly (by family members) promote the acceptance of irregular forms of employment entailing some form of tax evasion, and may lead to more frequent involvement in such forms of employment.
Keywords: J43; J49; H26; Z13; 330; temporary work; agricultural labor market; other specific labor markets; tax evasion; underground economy; economic sociology; Atypische Beschäftigung; Befristete Beschäftigung; Steuer; Steuervermeidung; Schattenwirtschaft; Ungarn